THE DEPICTION OF THE TEENAGERS` SOCIAL LIFE IN “HARRY POTTER” - Rajabov Akham Uktamovich; Jalilova Lola Jalilovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The given article deals with the psychological characteristics and depiction of teenagers` social life of the main hero in J.Rowling`s “Harry Potter and the Philosopher's Stone”. The characteristic features of modern children`s literature and specificity of children's literature are discussed. A vivid respond of modern children`s literature to the changes that society is now experiencing, and the depiction of realities in works of modern writers is investigated. A positive effect of children`s science fiction and fantasy literature on young generation is considered, the examples from the work are analyzed.